Age-dependent and regional heterogeneity in the long-chain base of A-series gangliosides observed in the rat brain using MALDI Imaging. Issue 1 (December 2017) - Caughlin, Sarah; Maheshwari, Shikhar; Weishaupt, Nina; Yeung, Ken; Cechetto, David; Whitehead, Shawn
Abstract Alterations in the long chain base of the sphingosine moiety of gangliosides have been shown to play a role in neurodevelopment and neurodegeneration. Indeed, the accumulation of d20:1 sphingosine has been referred to as a metabolic marker of aging in the brain, however, this remains to be shown in simple gangliosides GM2 and GM3. In this study, Matrix-assisted laser desorption/ionization Imaging Mass Spectrometry (MALDI IMS) was used to examine the neuroanatomical distribution of A-series gangliosides with either 18 or 20 carbon sphingosine chains (d18:1 or d20:1) in Fisher 344 rats across the lifespan. The ratio of d20:1/d18:1 species was determined across 11 regions of interest in the brain. Interestingly, a decrease in the d20:1/d18:1 ratio for GM2 and GM3 was observed during early development with the exception of the peri-ventricular corpus callosum, where an age-dependent increase was observed for ganglioside GM3. An age-dependent increase in d20:1 species was confirmed for complex gangliosides GM1 and GD1 with the most significant increase during early development and a high degree of anatomical heterogeneity during aging. The unique neuroanatomically-specific responses of d20:1 ganglioside abundance may lead to a better understanding of regional vulnerability to damage in the aging brain.